Larvicidal effectiveness of acethonilic and methanolic Ipomoea cairica extract using two extraction methods and its effects on the morphology of Culex quinquefasciatus Say mosquito - Wan Fatma Atma, Zuharah; Thiagaletchumi, Maniam; Nik, Fadzly; Sreeramanan, S.; Zary Shariman, Yahaya; Hamady, Dieng (Taylor and Francis Inc, 2017)
Plants produce a rich source of chemicals, drugs and secondary metabolites that can act as insect killer. The larvicidal activity of various part of Ipomoea cairica extracts was evaluated against Culex quinquefasciatus. The highest percentage of yield extract was given by Soxhlet with acetone solvent for all of the different plant parts. While, maceration technique only provided 1/3 of the yield compared to Soxhlet technique. Using 24 h larvicidal bioassay technique, third instar larvae of Cx. quinquefasciatus were exposed to concentrations ranging from 10 to 600 ppm of the acetone and methanol extracts of I. cairica from leaves, stem and flower bud. Acethonilic extract of I. cairica leaves was extracted using a Soxhlet apparatus which exhibited the most promising larvicidal activity against Cx. quinquefasciatus larvae with significantly lower LC50 value of 110.65 ppm, meanwhile methanolic leaves extract exhibited LC50 value of 143.47 ppm. Larvae exposed to the I. cairica extracts for 24 h showed morphological malformation that included a detachment of thorax, disruption of the digestive tract and pigmentation of cuticle on their death. Thus, suggested that I. cairica plant extract, especially acethonilic leaves extract can be considered as one of plant-derived insecticides for control of Cx. quinquefasciatus, a vector of filariasis.